In-use testing of disinfectants in hospitals - Prince, Jean (1972)
One hundred and five samples of clear, soluble phenolic disinfectants were obtained from varying sites in the wards of six hospitals. The concentration of disinfectant in each sample was measured by a colorimetric method and bacterial contamination was measured by an `in-use' test and a membrane filter technique. The concentrations of disinfectant in 24/105 (23%) samples were at the recommended level and 53 (50·5%) were below. Bacterial contamination with Gram-negative bacilli was found in 26/49 (53%) samples containing less than 0·8% of disinfectant and 5/86 (8·9%) samples containing more than 0·8%. The concentrations in two of the heavily contaminated samples were 1·5% and 1·6% respectively.